Control of a Nosocomial Outbreak of COVID-19 in a University Hospital. (22nd October 2020) - Harada, Sei; Uno, Shunsuke; Ando, Takayuki; Iida, Miho; Takano, Yaoko; Ishibashi, Yoshiki; Uwamino, Yoshifumi; Nishimura, Tomoyasu; Takeda, Ayano; Uchida, Sho; Hirata, Aya; Sata, Mizuki; et al.
Abstract: Background: Nosocomial spread of coronavirus disease 2019 (COVID-19) causes clusters of infection among high-risk individuals. Controlling this spread is critical to reducing COVID-19 morbidity and mortality. We describe an outbreak of COVID-19 in Keio University Hospital, Japan, and its control and propose effective control measures. Methods: When an outbreak was suspected, immediate isolation and thorough polymerase chain reaction (PCR) testing of patients and health care workers (HCWs) using an in-house system, together with extensive contact tracing and social distancing measures, were conducted. Nosocomial infections (NIs) were defined as having an onset or positive test after the fifth day of admission for patients and having high-risk contacts in our hospital for HCWs. We performed descriptive analyses for this outbreak. Results: Between March 24 and April 24, 2020, 27 of 562 tested patients were confirmed positive, of whom 5 (18.5%) were suspected as NIs. For HCWs, 52 of 697 tested positive, and 40 (76.9%) were considered NIs. Among transmissions, 95.5% were suspected of having occurred during the asymptomatic period. Large-scale isolation and testing at the first sign of outbreak terminated NIs. The number of secondary cases directly generated by a single primary case found before March 31 was 1.74, compared with 0 after April 1. Only 4 of 28 primary cases generated definite secondary infection; these were all asymptomatic. Conclusions: Viral shedding from asymptomatic cases played a major role in NIs. PCR screening of asymptomatic individuals helped clarify the pattern of spread. Immediate large-scale isolation, contact tracing, and social distancing measures were essential to containing outbreaks. Abstract : Asymptomatic transmissions played a major role in nosocomial COVID-19 infections among patients and healthcare workers. Large-scale isolation at the first sign of outbreak, rigorous contact tracing, extensive PCR testing, and strict distancing measures contributed to its containment.